Analysis of the Relationships Between Agricultural Producer Protection and Macroeconomic Variables in Fragile Five Countries by Bootstrap Panel Causality Test - Şerif Canbay (Journal of Agricultural Sciences)
Agriculture is a leading sector that provides capital accumulation to sustain the economic development processes of developing countries’ economies. The low supply and demand elasticity of agricultural products cause fluctuations in agricultural product prices and producer income. Therefore, the first negative reflection of price instability that may arise from fluctuations is generally observed in farmers. Hence, policymakers intervene in the agricultural sector to reduce the instability in agricultural product prices and protect agricultural producers against these effects, as well as the capital accumulation needed for growth and development. Based on this background, this study analyzes the causality relationship between agricultural producer protection (PP) and the macroeconomic variables of Brazil, Indonesia, India, Türkiye, and South Africa, which are referred to as the Fragile Five countries, using the panel bootstrap panel causality test developed by Kónya (2006) with the data between 2000 and 2020. The study findings differ among the countries in the sample. It was determined that there are causality relationships between agricultural PP and economic growth, economic development and inflation variables in all countries involved in this study. Although it is difficult to generalize the main findings of the study to all countries in the sample, it can be concluded that economic growth, economic development and inflation, and agricultural PP variables interact with one another. The study also concludes that the protective and supportive measures for agriculture, a significant sector for the macroeconomic performance indicators of the country’s economies, are too important to be neglected.